(567) Advanced Compiler Techniques - Lecture Notes تقنيات المترجم المتقدمة - ملاحظات المحاضرة - Lombardi, A. Lionello (INP, 2024)
The study explores various techniques for constructing compilers, emphasizing an interactive approach based on algebraic processing. Key topics include a thorough analysis of input-output considerations and the organization of executive routines to enhance performance. The study also introduces an efficient strategy for one-pass translation of Do-loops, reducing complexity and improving efficiency. Additionally, it highlights significant notes on the use of FORMAC, an advanced system for mathematical analysis, contributing to the development of comprehensive software solutions.